ANALISIS PRODUKTIVITAS PACKAGING MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) PADA MESIN AUTOCASE D-600 - Fakhri, Aditya; Septiani , Dyah Putri ‘Azizah (Universitas Majalengka, 2025)
In today’s food industry, machines need to run effectively to keep up with demand. At PT Indofood Sukses Makmur Tbk., Bogasari Division, the Autocase D-600 packaging machine is a key part of the Consumer Packing process. This study looks at how well the machine performs on line 1 and line 2 by using the Overall Equipment Effectiveness (OEE) method. Over 24 days, data on machine hours, downtime, production, and product defects were collected. The findings show that line 1 runs quite well, with many results close to global standards, while line 2 struggles because of frequent breakdowns, especially from faulty sensors. The study highlights the importance of preventive maintenance and operator training to keep performance high. In short, OEE helps the company see where improvements are needed to make packaging more efficient and productive.